Relational Personalization in Digital Gifted Learning: A PRISMA-Based Systematic Review of Meaning, Teacher Role, and the Paradox of Inclusivity - Kholidin, Farid Imam; Makaria, Eklys Cheseda; Rahmawati, Novi Rosita (Institut Agama Islam Negeri Kerinci, Indonesia, 2025)
Abstract. Digital transformation has fundamentally changed how gifted students interact with knowledge, yet emotional alienation and inequitable access persist despite technological opportunities. To systematically understand the meaning and experience of digital learning for gifted students through qualitative synthesis of international literature. Systematic searches were conducted in Scopus, Web of Science, ScienceDirect, MDPI, Taylor & Francis, and Google Scholar from January 2020 to September 2025. Peer-reviewed articles in English or Indonesian, published 2020-2025, focusing on digital learning for gifted/talented students in education, psychology, or learning technology fields, with full-text accessibility. Gifted students (high cognitive ability, above-average intellectual potential) engaged in digital learning environments across various educational contexts. Two independent reviewers conducted screening and selection following PRISMA 2020 guidelines. Quality assessment used the CASP Qualitative Checklist. From 312 identified articles, 10 studies met inclusion criteria after systematic review. Three major themes emerged: (1) cognitive autonomy coupled with emotional loneliness in digital environments; (2) teachers' evolving role as human mediators amid algorithmic learning; (3) paradoxical inclusivity—technology expands access but fails to guarantee social acceptance. These findings reveal digital gifted learning success depends not only on technological sophistication but also on educational systems' capacity to restore relational and empathetic dimensions. Literature predominantly represents global/Western contexts with limited representation from Indonesian or Islamic educational settings. Secondary data analysis restricts depth of affective experience understanding. Digital gifted learning requires